A rare case of temporal bone chondrosarcoma - Das, Amrutha V.; P. Joshi, Chinmayee; Patel, Brijal; Patel, Kalpesh B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
A rare case of lateral skullbase lesion, in a 24-year female, presented with moderately severe conductive type hearing loss, and facial paralysis. Audiological and radiological investigations were done which could not provide a reasonably certain diagnosis. So the patient was taken up for surgery. A subtotal pertrosectomy with blind sac closure was done. The histopathological analysis showed the lesion to be moderately differentiated chondrosracoma, an osseocartilagenous malignancy of the temporal bone. Due to rare nature, difficult location near vital structures, local invasiveness and potential for complications, diagnosis and treatment is difficult.